Artemis Fowl : the lost colony - Colfer, Eoin. (New York : Scholastic, 2007)
When demons begin appearing on Earth unpredictably, foreshadowing a cataclysmic breakdown of their magic, Artemis and his friends face a new foe--a twelve-year-old girl whose intellect just might match Artemis's own--as they try to prevent catastrophe.
"Miramax books."
G5
Keywords: Adventure and adventurers -- Fiction; Space and time -- Fiction; Fairies -- Fiction; Magic -- Fiction; Demonology -- Fiction